Studi Perencanaan Irigasi DAS Malaya di Kecamatan Lemong Kabupaten Pesisir Barat Provinsi Lampung Berbasis Sistem Informasi Geografis - Wicaksono, Steffanus Adrian Wibowo; Ridwan, Ridwan; Asmara, Sandi (Jurnal Agricultural Biosystem Engineering, 2023)
Pesisir Barat Regency has large land potential in agriculture sector, especially for rice cultivation, including in the administrative area of Lemong District. To increase the productivity of paddy fields at Lemong District, it is necessary to analyze the irrigation water needs. Therefore, research was carried out on the analysis of rice irrigation water needs and the river water discharge needed for irrigation.  The research was carried out in analysis stages including analysis of water balance using SWAT models which is integrated in the geographic information system, analysis of plant water needs, analysis of water irrigation needs, minimum discharge needed for land irrigation and analysis of water resource adequacy.  The research result show that the potential water resource in Lemong District can meet the irrigation water needs of rice cultivation in two planting seasons with coverrage area that can be developed of 76.42 hectares. Meanwhile, in the third planting season for planting of secondary crops, the potential of river discharge is only sufficient for 19 hectares and in order for the target planting area of 76.42 hectares to be archieved it is necessery to add irrigation originating from ground water (pump irrigation) with discharge of 0.51 m3/sec. Keywords: Geographic information system, Irrigation, SWAT.